A Single‐Center Study on Frontline Treatment for Multiple Myeloma Patients With 1q Abnormalities - Ashish Patel; Esther Masih‐Khan; Adam Smith; Katherine Lajkosz; Sita Bhella; Christine Chen; Anca Prica; Donna Reece; A. Keith Stewart; Roger Tiedemann; Suzanne Trudel; Chloe Yang; et al. (eJHaem)
ABSTRACT Introduction Chromosome 1q copy gains (with‐1q‐gain) is a frequently observed genetic abnormality in multiple myeloma (MM) patients. Recent research has demonstrated that 1q gain is a prognostic factor, linked to poorer clinical outcomes. Methods This study was conducted at the Princess Margaret Cancer Centre to examine the clinical outcomes of newly diagnosed MM patients’ with‐1q‐gain or without‐1q‐gain abnormality. The study included 275 patients, with 161 (58.5%) with‐1q‐gain abnormality. The median follow‐up time for the cohort was 94.3 months (95% CI 30.1–38.6). Results The patients’ with‐1q‐gain when compared to without‐1q‐gain were more likely to have other high‐risk cytogenetic abnormalities (34.8% vs. 14.0%, p < 0.001) and more advanced disease according to the International Staging System (ISS III, p < 0.014). Furthermore, a relatively higher proportion of with‐1q‐gain patients received tandem autologous stem cell transplant (ASCT) as frontline therapy (36.2% vs. 8.7%, p ≤ 0.001). To assess the impact of 1q copy number, patients with 3 copies of 1q (1q‐gain3) were compared to those with ≥4 copies (1q‐Amp). No significant differences were observed between the two groups. Conclusion In conclusion, our study provides insight into the clinical significance of 1q gain abnormality in MM patients at a single center, and highlights its association with adverse prognostic features and treatment outcomes.